Comparison of Samfilcon A and Balafilcon A Bandage Contact Lenses in Reducing Postoperative Symptoms After Pterygium Surgery - Yao TY; Wang JS; Xie HT; Zhang MC (Clinical Optometry)
Tian-Yu Yao, Jia-Song Wang, Hua-Tao Xie, Ming-Chang Zhang Department of Ophthalmology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of ChinaCorrespondence: Hua-Tao Xie; Ming-Chang Zhang, Department of Ophthalmology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China, Tel +86-27-85726662, Email huataoxie@hust.edu.cn; mingc_zhang@hust.edu.cnObjective: To compare differences in postoperative pain, foreign body sensation, photophobia, and lacrimation between balafilcon A and samfilcon A bandage contact lenses (BCLs) in the early stage following pterygium surgery.Methods: A total of 66 eyes with pterygium conjunctival grafts fixed with sutures were included in this study, comprising 32 eyes fixed with samfilcon A and 34 eyes fixed with balafilcon A. Demographic data, postoperative corneal epithelialization time, and subjective discomfort, such as pain (using the visual analog scale [VAS]), were recorded and compared.Results: Significant differences were noted in VAS scores between the first day (P< 0.01) and the second day post-surgery (P=0.03), suggesting that patients experienced less pain after wearing samfilcon A. However, no significant differences were observed in corneal epithelialization time, VAS score before lens removal, foreign body sensation, photophobia, lacrimation, insomnia, and demographic data between the two groups. Finally, only two balafilcon A patients required nonsteroidal analgesics.Conclusion: After pterygium surgery, samfilcon A BCL was associated with lower pain levels compared with balafilcon A BCL and could assist in reducing postoperative discomfort in patients and concurrently improving patient satisfaction.Keywords: bandage contact lenses, pterygium, pain, visual analog scale, samfilcon A, balafilcon A